Improving output performance of a two-switch forward converter with a lead-lag controller - Wuti, V.; Bunlaksananusorn, C. (My University, 2015)
This paper presents improvement of an output performance of a two-switch forward converter with a Lead-Lag (LL) controller. The controller design is illustrated and its ability to regulate the converter's output voltage is evaluated experimentally. It is revealed that the converter employing the LL controller can achieve a higher system bandwidth compared to that employing the Proportional-plus-Integral (PI) controller, therefore exhibiting a faster output voltage response.
Keywords: controller design; Lead-Lag controller; PI controller; two-switch forward converter